Construction and Validation of Duâ Scale for Pakistani Muslim Adults - Tahir, Wajeeha (Journal of religion and health, 2025)
Duâ, an act of worship, signifies a profound connection between an individual and their Creator, reflecting trust in God’s power and will. It encompasses dimensions such as quantity, style, purpose, and target. This research aimed to develop reliable measures of duâ for Pakistani Muslim adults using a mixed− method exploratory sequential design across two studies. Study 1 was conducted in three phases. In Phase 1, thematic analysis was conducted using qualitative methods such as focus group discussions, semi-structured interviews, and insights from pertinent theoretical framework. This analysis identified seven themes for duâ, aligning with existing literature on prayer experiences. Based on these themes, an initial set of 70 items for the duâ scale (DS) was developed. Phase 2 focused on translating and cross-validating the Prayer Importance Scale, Tatmainn al-Qulūb Scale, and Brief Trust vs. Mistrust in God Scale. In Phase 3, the content-validated item pool of 67 items was administered to a large sample of Pakistani Muslim adults (N = 461) and analyzed through exploratory factor analysis (EFA). EFA revealed 7-factor structure factor loading (with item loading .49 to .87) of the DS containing 40 items with a cumulative variance of 61.10%. Factors including prayer quantity (3 items); free prayer style (5 items); bounded prayer style (8 items); outward prayer purpose (7 items); inward prayer purpose (5 items); engaged prayer target (7 items) and distant prayer target (5 items). Duâ showed a significant positive correlation with centrality of religiosity, importance of prayer, and trust in God, and a non-significant correlation with mistrust in God, supporting the convergent and discriminant validity of the DS. In the second study (N = 703), confirmatory factor analysis (CFA) confirmed the scale’s structure, matching the exploratory factor analysis (EFA) with 40 items and 7 subscales. In the final measurement model, all constructs had an average variance extracted (AVE) greater than .50, and maximum shared variance (MSV) values were lower than the AVE. The diagonal values of the square root of the AVE exceeded the intercorrelations, confirming the DS as a reliable and valid measure of duâ. Evidence for the measurement invariance of DS suggested its consistency and comparability across Sunni and Non-Sunni Muslims. Further research is recommended to explore its application across different religious sects and ethnic groups globally.